PENGEMBANGAN MEDIA PUZZLE PANCASILA (PUZZPALA) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 2 SEKOLAH DASAR - Cicik Amoret Agripina; Tety Nur Cholifah (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2020)
This research aims to develop learning media products in the form of Valid Pancasila Puzzles used in togetherness materials at home to improve students' learning outcomes.. The benefits of Pancasila Puzzle media can be a source of learning and improve students' learning outcomes. This research uses rnd research type (Research and Development) according to Sugiyono with 10 stages of development according to Sugiyono as follows (1) Potential and problems; (2) Data collection; (3) Product design; (4) Validasi design; (5) Design revision; (6) Usage trial; (7) Product revision; (8) Usage trial; (9) Product revision; (10) Mass production. The results showed that pancasila puzzle media deserves to be a learning medium with a percentage of eligibility provided by media experts which is 93% and by material experts 85% with very valid and feasible criteria. The results of large-scale trials saw a 69% increase in study results, with an average of 63 pretestand 87 posttest results.Individual trials with student response questionnaires on the use of pancasila puzzle media show a percentage of 100% categorized as highly feasible